2009
DOI: 10.1590/s1808-86942009000600018
|View full text |Cite
|
Sign up to set email alerts
|

Protocolo para captação dos potenciais evocados auditivos de longa latência

Abstract: Long Latency Auditory Evoked Potentials (LLAEP) represents a number of electrical changes occurring in the central nervous system, resulting from stimulation of the auditory sensorial pathways. Many studies approach the use of these potentials controlling the artifact created by eye movement with the use of equipment with a large number of channels. However, what happens is very different in Brazilian clinical practice, where the equipment used has a very limited number of channels. Aim: to compare the two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Despite the hemispheric differentiation and undeniable inequality in functional importance of the cerebral hemispheres, there were no differences between the performance of the right and left ears in the present study. Other studies have reported the absence of differences between ears, 10 , 11 , 12 so the discussion will focus on the comparison between speech stimuli and tone burst, regarding the latency of exogenous components, and the latency and amplitude of the endogenous component P3.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the hemispheric differentiation and undeniable inequality in functional importance of the cerebral hemispheres, there were no differences between the performance of the right and left ears in the present study. Other studies have reported the absence of differences between ears, 10 , 11 , 12 so the discussion will focus on the comparison between speech stimuli and tone burst, regarding the latency of exogenous components, and the latency and amplitude of the endogenous component P3.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they consist of a series of positive and negative peaks which take place from 50 ms after the stimulus onset and can be useful in investigating neural mechanisms related to auditory perception (1,2) …”
mentioning
confidence: 99%
“…According to the authors, clinical participants should be selected according to clear and well established diagnostic criteria, and samples should be as homogeneous as possible (1) . The literature suggests that the controls selected in the studies should differ from the clinical group only regarding the variable of interest and the drugs used by the subjects should be documented.…”
mentioning
confidence: 99%
“…A avaliação dos PEALL pode ser realizada utilizando-se estímulos verbais ou não verbais. Quando realizado com estímulos de fala, fornecem informações a respeito dos processos relacionados à codificação e decodificação da fala no sistema auditivo central, auxiliando na identificação de alterações de detecção e discriminação de fala (ALVARENGA et al, 2013;DIDONÉ et al, 2015;TREMBLAY;KORCZAK, 2008;SILVA et al, 2017). Além disso, há estudos que apontam que quanto maior é a demanda com relação ao processamento da tarefa e mais difíceis e complexos são os "alvos" a serem discriminados, maior é a latência do P300 e menor sua amplitude (DIDONÉ et al, 2015;MASSA et al, 2011).…”
Section: Potenciais Evocados Auditivos De Longa Latência (Peall)unclassified